Splenic metabolic activity predicts risk of future cardiovascular events: demonstration of a cardiosplenic axis in humans - Emami, Hamed; Singh, Parmanand; MacNabb, Megan; Vucic, Esad; Lavender, Zachary; Rudd, James H F; Fayad, Zahi A; Lehrer-Graiwer, Joshua; Korsgren, Magnus; Figueroa, Amparo L; Fredrickson, Jill; Rubin, Barry; et al. (JACC. Cardiovascular imaging, 2015)
This study sought to determine whether splenic activation after acute coronary syndrome (ACS) is linked to leukocyte proinflammatory remodeling and whether splenic activity independently predicts the risk of cardiovascular disease (CVD) events. Pre-clinical data suggest the existence of a cardiosplenic axis, wherein activation of hematopoietic tissues (notably in the spleen) results in liberation of proinflammatory leukocytes and accelerated atherosclerotic inflammation. However, it is presently unknown whether a cardiosplenic axis exists in humans and whether splenic activation relates to CVD risk. (18)F-fluorodeoxyglucose ((18)FDG)-positron emission tomography (PET) imaging was performed in 508 individuals across 2 studies. In the first study, we performed FDG-PET imaging in 22 patients with recent ACS and 22 control subjects. FDG uptake was measured in spleen and arterial wall, whereas proinflammatory gene expression of circulating leukocytes was assessed by quantitative real-time polymerase chain reaction. In a second study, we examined the relationship between splenic tissue FDG uptake with subsequent CVD events during follow-up (median 4 years) in 464 patients who previously had undergone FDG-PET imaging. Splenic activity increased after ACS and was significantly associated with multiple indices of inflammation: 1) up-regulated gene expression of proinflammatory leukocytes; 2) increased C-reactive protein; and 3) increased arterial wall inflammation (FDG uptake). Moreover, in the second study, splenic activity (greater than or equal to the median) was associated with an increased risk of CVD events (hazard ratio [HR]: 3.3; 95% confidence interval [CI]: 1.5 to 7.3; p = 0.003), which remained significant after adjustment for CVD risk factors (HR: 2.26; 95% CI: 1.01 to 5.06; p = 0.04) and for arterial FDG uptake (HR: 2.68; 95% CI: 1.5 to 7.4; p = 0.02). Our findings demonstrate increased splenic metabolic activity after ACS and its association with proinflammatory remodeling of circulating leukocytes. Moreover, we observed that metabolic activity of the spleen independently predicted risk of subsequent CVD events. Collectively, these findings provide evidence of a cardiosplenic axis in humans similar to that shown in pre-clinical studies.